INTRODUCING ANTIOXIDANTS AS ESSENTIAL FOR THE MAINTENANCE OF TISSUE LIFE AS DEMONSTRATED IN HUMAN HAIR FOLLICLES - A , Abraham (International Journal of Research -GRANTHAALAYAH, 2018)
Hair Follicles have been described as mini-organs having a wide range of functions and relying in tightly regulated molecular signaling for its metabolism, and extensively described to emit biomagnetic fields (BMFs). The ubiquitous enzyme catalase is essential for the eukaryotic cells to maintain toxic Reactive Oxygen Species (such as H2O2) in equilibrium. This manuscript presents a novel optical microscopy technique that utilizes a glass slide sandwich (SDW) where drops of fresh human blood are trapped. Drops of water are placed on the top slide of the SDW, in which a freshly plucked human hair follicle is immersed. In this experimental model, is shown that in water immersed follicles, BMFs interact with the intrinsic BMFs of the blood, this in turn causing vertically detected spatial images resembling two different magnetic profiles (MPs). When hairs are immersed in 35% H2O2 oxygen bubbles (O2) are displayed due to the H2O2 breakdown by the enzyme catalase. When the O2 breakdown ceases is theorized that tissue death has occurred. Results are presented of images and video-recordings correlating the absence of catalase with cessation of MPs.